Manajemen Perilaku Organisasi Dalam Mewujudkan Sumber Daya Manusia Yang Kompeten Di SD Negeri 14 Talago Gunung Kota Sawahlunto - Ermida, Ermida; Hendriani, Suswati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The aims of this research are 1. To describe the organizational behavior management of SD Negeri 14 Talago Gunung Kota Sawahlunto to create human resources. 2) Analyze the obstacles and solutions in this study. The results of the study revealed about the Management of Organizational Behavior at SD Negeri 14 Talago Gunung Sawahlunto City in realizing human resources which was carried out by planning; carried out by conducting an analysis of the activities or work load of intellectual capacity, work experience and example. Recruitment; prioritizing academic & non-academic achievements, having good character, putting aside kinship and prioritizing achievement and professionalism. 1. Development, namely changing behavior so that change occurs, attending workshops, training and training. 2. Supervision is carried out according to a monthly schedule for the entire series of school activities, the condition of students, infrastructure, teachers, programs, facilities. 3. Evaluation; three stages: monthly, midterm and end of semester, as well as the end of the academic year. 4. Barriers; Teachers are not as expected, lack of teacher motivation to show competence, not yet mastered IT, lack of teacher competence, development of teacher training, other workshop activities